Advances in Spin Catalysts for Oxygen Evolution and Reduction Reactions. Issue 5 (23rd November 2022) - Bai, Haoyun; Feng, Jinxian; Liu, Di; Zhou, Pengfei; Wu, Rucheng; Kwok, Chi Tat; Ip, Weng Fai; Feng, Wenlin; Sui, Xulei; Liu, Hongchao; Pan, Hui
Abstract: Searching for high effective catalysts has been an endless effort to improve the efficiency of green energy harvesting and degradation of pollutants. In the past decades, tremendous strategies are explored to achieve high effective catalysts, and various theoretical understandings are proposed for the improved activity. As the catalytic reaction occurs at the surface or edge, the unsaturated ions may lead to the fluctuation of spin. Meanwhile, transition metals in catalysts have diverse spin states and may yield the spin effects. Therefore, the role of spin or magnetic moment should be carefully examined. In this review, the recent development of spin catalysts is discussed to give an insightful view on the origins for the improved catalytic activity. First, a brief introduction on the applications and advances in spin‐related catalytic phenomena, is given, and then the fundamental principles of spin catalysts and magnetic fields‐radical reactions are introduced in the second part. The spin‐related catalytic performance reported in oxygen evolution/reduction reaction (OER/ORR) is systematically discussed in the third part, and general rules are summarized accordingly. Finally, the challenges and perspectives are given. This review may provide an insightful understanding of the microscopic mechanisms of catalytic phenomena and guide the design of spin‐related catalysts. Abstract : The review systematically summarizes the recent development of spin catalysts for oxygen evolution/reduction reaction (OER/ORR) from both experimental and theoretical views. General rules and strategies to control the spin states for improved catalytic performance are carefully summarized and discussed.